Molecular characterization of siderophore biosynthesis in Paracoccidioides brasiliensis - Marielle Garcia Silva; Juliana Santana de Curcio; Mirelle Garcia Silva-Bailão; Raisa Melo Lima; Mariana Vieira Tomazett; Aparecido Ferreira de Souza; Vanessa Rafaela Milhomem Cruz-Leite; Nicolau Sbaraini; Alexandre Melo Bailão; Fernando Rodrigues; Maristela Pereira; Relber Aguiar Gonçales; et al. (IMA Fungus)
Abstract Iron is an essential nutrient for all organisms. For pathogenic fungi, iron is essential for the success of infection. Thus, these organisms have developed high affinity iron uptake mechanisms to deal with metal deprivation imposed by the host. Siderophore production is one of the mechanisms that fungal pathogens employ for iron acquisition. Paracoccidioides spp. present orthologous genes encoding the enzymes necessary for the biosynthesis of hydroxamates, and plasma membrane proteins related to the transport of these molecules. All these genes are induced in iron deprivation. In addition, it has been observed that Paracoccidioides spp. are able to use siderophores to scavenge iron. Here we observed that addition of the xenosiderophore ferrioxamine B FOB) to P. brasiliensis culture medium results in repression (at RNA and protein levels) of the SidA, the first enzyme of the siderophore biosynthesis pathway. Furthermore, SidA activity was reduced in the presence of FOB, suggesting that P. brasiliensis blocks siderophores biosynthesis and can explore siderophores in the environment to scavenge iron. In order to support the importance of siderophores on Paracoccidioides sp. life and infection cycle, silenced mutants for the sidA gene were obtained by antisense RNA technology. The obtained AsSidA strains displayed decreased siderophore biosynthesis in iron deprivation conditions and reduced virulence to an invertebrate model.